North Coast of Trinidad - (:unkn) unknown (Stephens and Todd Ltd. and Yuille's Printerie Ltd., 2009)
A picture showing the rugged coastline of Trinidad's north coast from the North Coast road.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coasts--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; Bodies of water--Trinidad and Tobago